2014
DOI: 10.4236/ajps.2014.54062
|View full text |Cite
|
Sign up to set email alerts
|

The Transfer of Cu, Zn, Mn and Fe between Soils and <i>Allium</i> Plants (Garlic and Onion), and Tomato in the Southwest of the Buenos Aires Province, Argentina

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Recent studies ( Kataeva et al , 2012 ; Moralejo and Acebal, 2014 ) have shown high concentrations of heavy metals (Cu, Pb, Cd, Ni) in aquatic environments with pesticide use, leading to changes in cell division processes and chromosome abnormalities. The chemical contaminants in the studied stream water might be responsible for the genetic changes (micronuclei, DNA damage and chromosomal change) observed in the A. cepa and A. altiparanae bioassays.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies ( Kataeva et al , 2012 ; Moralejo and Acebal, 2014 ) have shown high concentrations of heavy metals (Cu, Pb, Cd, Ni) in aquatic environments with pesticide use, leading to changes in cell division processes and chromosome abnormalities. The chemical contaminants in the studied stream water might be responsible for the genetic changes (micronuclei, DNA damage and chromosomal change) observed in the A. cepa and A. altiparanae bioassays.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed an extensive DNA smearing in both cell lines exposed to untreated and treated (pH-neutralised) AMD at 75%, 50% (RTgill-W1) and 50% (Vero) concentrations. The water sample U had considerable genotoxic potential, both in the damage index and the frequency index, when compared to T; although the active treatment method (in-stream pH neutralisation) significantly reduced DNA damage in T (Figs 1 and 2), this was not enough to prevent observable DNA damage sustained in T. A plausible explanation could be the persistence of non-precipitated substances and/or heavy metals that interact with other solutes to form complexes which remain in the dissolved form, being potentially able to attack nucleic acids (Moralejo and Acebal, 2014). A previous study by Steyn et al (2019) demonstrated that treated AMD was toxic for up to 7 km downstream of a treatment plant along Tweelopie stream, failing to effectively protect ecosystem health.…”
Section: Discussionmentioning
confidence: 99%